(untitled) (Journal of Economic Research & Business Administration, 2016)
The main tool of monetary policy to maintain the planned level of inflation - the manipulation of accounting rate (the refinancing rate). Thus, the increase in the discount rate increases deposit rates at commercial banks and increases the attractiveness of saving money rather than spend-ing. Lowering the discount rate reduces deposit rates at commercial banks and reduce the attractiveness of saving money. In addition, the increase in interest rates increases the interest rate of credit in the banks and reduces the demand for loans. Lowering the dis-count rate allows financial institutions to reduce lending rates. Thus, there is an increase in the quantity of money held by the public; respectively, reducing the discount rate increases the rate of inflation. Increasing the discount rate decreases the rate of inflation.